Ultrasensitive determination of amoxicillin using chemiluminescence with flow injection analysis. Issue 1 (2006) - Xie Xie, Xiaofeng Xiaofeng; Song Song, Zhenghua Zhenghua
Abstract : Results presented here reveal that amoxicillin can greatly enhance the chemiluminescence intensity generated from the reaction between luminol and hydrogen peroxide. The increment chemiluminescence signal was linearly dependent on amoxicillin concentration in the range from 10 pg·ml −1 to 2 ng·ml −1 (r 2 =0.9978) offering a detection limit as low as 3.5 pg·ml −1 (3σ). At a flow rate of 2.0 ml·min −1, one analysis cycle, including sampling and washing, can be accomplished in 20 s with a relative standard deviation of less than 5%. The sensitive flow injection method was applied successfully to determine of amoxicillin in pharmaceutical preparations, human urine and serum without any pretreatment procedure, with recovery from 90.0% to 110.0% and relative standard deviations of less than 5.0%.